Biogeographical analyses to facilitate targeted conservation of orchid diversity hotspots in Costa Rica - Crain, Benjamin J. (2020)
Aim: We conduct a biogeographical assessment of orchids in a global biodiversity hotspot to explore their distribution and occurrences of local hotspots while identifying geographic attributes underpinning diversity patterns. We evaluate habitat characteristics associated with orchid diversity hotspots and make comparisons to other centres of orchid diversity to test for global trends. The ultimate goal was to identify an overall set of parameters that effectively characterize critical habitats to target in local and global orchid conservation efforts. Location: Costa Rica; Mesoamerica. Taxon: Orchidaceae. Methods: Data from an extensive set of herbarium records were used to map orchid distributions and to identify diversity hotspots. Hotspot data were combined with geographic attribute data, including environmental and geopolitical variables, and a random forest regression model was utilized to assess the importance of each variable for explaining the distribution of orchid hotspots. A likelihood model was created based on variable importance to identify locations where suitable habitats and unidentified orchid hotspots might occur. Results: Orchids were widely distributed and hotspots occurred primarily in mountainous regions, but occasionally at lower elevations. Precipitation and vegetation cover were the most important predictive variables associated with orchid hotspots. Variable values underpinning Costa Rican orchid hotspots were similar to those reported at other sites worldwide. Models also identified suitable habitats for sustaining orchid diversity that occurred outside of known hotspots and protected areas. Main conclusions: Several orchid diversity hotspots and potentially suitable habitats occur outside of known distributions and/or protected areas. Recognition of these sites and their associated geographic attributes provides clear targets for optimizing orchid conservation efforts in Costa Rica, although certain caveats warrant consideration. Habitats linked with orchid hotspots in Costa Rica were similar to those documented elsewhere, suggesting the existence of a common biogeographical trend regarding critical habitats for orchid conservation in disparate tropical regions.